Assessment of stress coping strategies of handicapped sportsmen based on different variables - Meric Eraslan; Tonguc Vardar; Atilla Pulur (Selcuk University, 2017)
This study aims to evaluate stress coping strategies of handicapped sportsmen based on certain demographic variables. A total of 261 licensed and active sportsmen, 204 male and 57 female, who are undergoing regular training from different branches of sports including amputee football, wheelchair basketball, swimming and other fields participated in this research. "Stress Coping Strategies Scale" which was developed by Lazarus amp; Folkman and adapted to Turkish by Şahin amp; Durak was used in this research. Whitney U test and Kruskal Wallis H test was used for statistical analysis of data collected. As a result of this research, it was understood that handicapped sportsmen moderately used confident attitude, desperate attitude, submissive attitude, request for social support and optimist attitude. It was also understood that stress coping strategies of handicapped sportsmen who participated in the research have significant differences based on their age, gender, branch of sports and years spent doing sports (p lt;0.05). As a result, we might suggest that age, gender, branch of sports and years spent doing sports are important factors that affect the stress coping strategies of sportsmen.